1983
DOI: 10.1099/0022-1317-64-6-1229
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Single- and Double-stranded Hepatitis B Virus DNA and Viral Antigen Accumulation in Infected Liver Cells

Abstract: SUMMARYLiver sections from five patients with persistent hepatitis B virus (HBV) infection and active cirrhosis were shown to contain intracellular HBV DNA by in situ hybridization using cloned 3H-labelled HBV DNA probes. Two classes of infected cells, with different distributions throughout the liver, were distinguished: (i) cells containing a low copy number of double-stranded HBV nucleotide sequences, confined to the cell nucleus and thought to represent HBV DNA, and (ii) cells containing large amounts (est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
5
25
0
Order By: Relevance
“…These findings were not confirmed in the present study. The result on the predominant cytoplasmic detection of HBV-DNA in hepatocytes was consistent with other reports on the detection of HBV-DNA by in situ hybridization using radiolabeled probes (3,7,10,11,17). It is thought that the replication cycle of HBV-DNA in hepatocytes resembles in some ways retroviruses replicating in the cytoplasm (22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings were not confirmed in the present study. The result on the predominant cytoplasmic detection of HBV-DNA in hepatocytes was consistent with other reports on the detection of HBV-DNA by in situ hybridization using radiolabeled probes (3,7,10,11,17). It is thought that the replication cycle of HBV-DNA in hepatocytes resembles in some ways retroviruses replicating in the cytoplasm (22).…”
Section: Discussionsupporting
confidence: 91%
“…It is likely that assay by in situ hybridization is not so highly sensitive as by Southern or dot blot hybridization using radiolabeled or biotinylated probes (6,10,11,18). Therefore in situ hybridization for the detection of HBV-DNA in hepatocytes seems to be detectable in the hepatocytes containing a large amount of free replicating form of HBV-DNA (10,11,18). It was described in one report that HBV-DNA was not only detected in the hepatocytes but also bile duct epithelial cells and vascular elements (2).…”
Section: Discussionmentioning
confidence: 99%
“…From the intensity of this band relative to standards of known concentration we estimated that on average -50 molecules of HBV DNA per cell were present in the piece of liver analysed. The number of HBV DNA molecules in hepatocytes supporting HBV replication has been estimated by in situ hybridization to be several hundreds to several thousands (Burrell et al, 1982;Blum et al, 1983), but it has also been observed that not all hepatocytes supported HBV replication (Gowans et al, 1983). Thus it is likely that only a fraction of the hepatocytes in the liver biopsy used for DNA and RNA extraction was productively infected, and that the number of HBV genomes (-50) and HBV transcripts (20-50) per infected cell is in fact much higher.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously examined several liv ers with markers of virus replication by in situ hybridization; since our original observation [2] that the bulk of HBV DNA in infected hepatocytes was localized in the cytoplasm, we have shown that much of this viral DN A is single-stranded and probably represents re plicative intermediates [3]. Furthermore, nuclei that were strongly positive for HBcAg by immunofluorescence contained little, if any, detectable viral DNA, although the cytoplasm of the same cells was often positive for viral DNA [3].…”
mentioning
confidence: 99%
“…Furthermore, nuclei that were strongly positive for HBcAg by immunofluorescence contained little, if any, detectable viral DNA, although the cytoplasm of the same cells was often positive for viral DNA [3]. However, in that study HBcAg was detected by direct immunofluorescence, a technique lacking in sensitivity [4], By using a recently available high-titer rabbit anti-HBc in indirect immu nofluorescence or in peroxidase-antiperoxi dase (PAP) reactions, we have detected more widespread cytoplasmic HBcAg than was previously found by direct immunofluores cence [4].…”
mentioning
confidence: 99%